Four weeks of training with simple postural instructions changes trunk posture and foot strike pattern in recreational runners. (January 2019) - Shih, Hui-Ting; Teng, Hsiang-Ling; Gray, Casey; Poggemiller, Matthew; Tracy, Ian; Lee, Szu-Ping
Abstract: Objectives: Previous studies showed that adopting forward trunk lean and forefoot strike patterns may reduce risk of running-related knee injuries. However, the process of learning such forms is unclear. The purpose of the study was to investigate the effects of a 4-week training using simple postural instructions to elicit these changes. Design: Longitudinal intervention study. Setting: A training included postural instructions: 1) lean your trunk forward, and 2) land on the front part of your feet. Participants: Eighteen recreational runners. Main outcome measures: Participants were assessed prior to training (PRE), immediately after the instructions (iPST), during training at 2 weeks (2WK) and 4 weeks (4WK), and 7–10 days after the conclusion of training (RET). Assessment consisted of running trials performed at self-selected and controlled speeds, during which the trunk and foot strike angles were assessed. Results: Comparing to PRE, forward trunk angle significantly increased by approximately 3.5° and foot strike angle by approximately 7° at 2WK, 4WK and RET. Conclusions: A 4-week training with simple postural instructions induced significant changes in trunk and foot strike patterns in recreational runners. Future study is needed to develop clinical therapeutic protocols for runners with and at risk of running-related knee injuries. Highlights: Four-week training with posture instructions enabled recreational runners to adopt increased trunk flexion. Four-week training with posture instructions also successfully elicited anterior foot strike. Learning effect was confirmed by the retained learned running forms, one week after conclusion of training. The changes in trunk lean and foot strike pattern did not translate to significant reduction in GRF.